ETIKA MARKETING DALAM PERSPEKTIF EKONOMI ISLAM - Malahayatie Malahayatie; Maryamah Maryamah (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2019)
Marketing is a human activity that is directed to meet the needs and desires through the exchange process. While marketing in the view of Islam is an application of strategic discipline in accordance with sharia values ​​and principles. Assessment of business success is not only determined by increasing economic and financial achievements, but success must also be measured through benchmarks of morality and ethical values ​​on the basis of social values ​​in religion. The type of this research is library research (library research), which is a data collection which is carried out directly on an object to obtain data. This research uses a normative approach which is research based on theories and marketing concepts in Islam. From the results of this discussion it was concluded that, Islamic marketing teaches marketers to be honest with consumers or others. Sharia values ​​prevent marketers from falling into values ​​that must be upheld by a marketer. Four forms of marketing in Islamic Economic Ethics that guide marketing as Rabbaniyah, Akhlaqiyyah, Al-Waqiyyah and Insaniyyah. Some things that must be considered as marketing ethics in the perspective of Islamic economics are having a good and spiritual personality (taqwa), being fair in business, having a good personality and and respecting people's rights and property correctly, serving consumers humbly, always keeping promises and no cheating in marketing, honest and trustworthy and not excessive in advertising goods, do not like to prejudice and bad-mouthing the merchandise of others, do not make bribes (risywah), all forms of marketing activities must provide benefits to many parties and cooperate with each other and provide benefits with the aim of welfare among fellow entrepreneurs.